2021
DOI: 10.1007/s12144-021-01837-x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting university students’ well-being and studying with an acceptance and commitment therapy (ACT)-based intervention

Abstract: Students’ poor well-being is a serious problem in higher education. In part, this problem is related to the problems in studying as poorer study skills are related to poorer well-being. Both students’ study skills and their well-being should be enhanced in higher education, but effective ways to do this are needed. The aim of this study was to explore students’ experiences of an ACT-based online, 8-week course on university students’ well-being and studying. Data were collected in two ways: a) with qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…In addition to improving students’ well-being and studying in several ways ( Asikainen et al, 2019 ; Katajavuori et al, 2021 ), an ACT-based intervention combined with time management training in the higher education context can be a beneficial way to diminish procrastination in the academic context. These kinds of courses are able to improve time management and psychological flexibility skills, which can be considered very important future working life skills as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to improving students’ well-being and studying in several ways ( Asikainen et al, 2019 ; Katajavuori et al, 2021 ), an ACT-based intervention combined with time management training in the higher education context can be a beneficial way to diminish procrastination in the academic context. These kinds of courses are able to improve time management and psychological flexibility skills, which can be considered very important future working life skills as well.…”
Section: Discussionmentioning
confidence: 99%
“…We expect that the ACT-based course, which includes time management training, has an impact on students’ time management skills ( Häfner et al, 2015 ), psychological flexibility ( Räsänen et al, 2016 ) and procrastination ( Gagnon et al, 2016 ). In addition, we expect that both psychological flexibility and time management skills have an effect on procrastination during the course ( Hailikari et al, 2021 ; Katajavuori et al, 2021 ).…”
Section: Research Questionsmentioning
confidence: 99%
“…Similarly, Fang and Ding (2020a) discovered that junior high school students who took part in an ACT intervention group experienced greater gains in their school engagement and psychological capital (i.e., self-efficacy, optimism, hope, resilience) compared to the control group. Katajavuori et al (2021) reported an increase in university students' skills related to time and stress management, studying, and coping with negative thoughts after an online ACT-based intervention program. Kiuru et al (2021) reported a decrease in adolescents' career-related insecurity after an online ACT-based intervention program.…”
Section: Acceptance and Commitment Therapy In Supporting Well-being A...mentioning
confidence: 96%
“…Taken together, therefore, it is critical to enhance our knowledge of the predictors of psychological wellbeing among learners, which have been seen as the essential source of learning achievement, particularly among the university students ( Bewick et al, 2010 ; Li, 2022 ). More importantly, researchers have cautioned that poor wellbeing among students in higher education (i.e., university students) has become a profound issue that merits further investigation ( Katajavuori et al, 2023 ). Appropriately, it is vital to address the antecedents of psychological wellbeing among students in higher education as an attempt to enhance this positive experience in classrooms.…”
Section: Introductionmentioning
confidence: 99%